Synthesis, characterization, spectral studies and antifungal activity of Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II) complexes with 2-(4-sulphophenylazo)-1,8-dihydroxy-3,6-napthalene disulphonic acid trisodium salt - Pandey G.; Narang K.K. (My University, 2025)
Complexes of the type Na6[M(HL)2(H2O) 2], where M= Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II)and Na3H2L= 2-(4-sulphophenylazo)-1,8-dihydroxy 3,6 naphthalene disulphonic acid trisodium salt, havebeen synthesized and characterized by physico-chemical (elemental analyses, solubility, electrolyticconductance, magnetic susceptibility measurement) and spectral (UV-Visible, IR, ESR, powder x-raydiffraction) techniques for their structure and studied for their antifungal activity against ten fungi. Theanionic 1:2 metal:ligand complexes show octahedral geometry around M(II), a significant antifungal activityagainst Curvularia lunata and Alternaria triticina and a moderate activity against Alternaria brassicicola,Alternaria brassicae, Alternaria solanae, Curvularia species, Helminthosporium oryzae, Collectotrichumcapsici, Aspergillus niger, Aspergillus flavus and Fusarium udum.